EVALUATION OF MANAGEMENT AND WELFARE LEVEL OF SAMBAR DEER IN PALANGKA RAYA CAPTIVITY - Asri Pudjirahaju; Heri Sujoko; Siti Ma’rifah (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Sambar deer (Rusa unicolor) is one of four native deer species in Indonesia that are protected. The conservation status of the International Union for Conservation of Nature (IUCN) in the wild is categorized as an endangered species with the status Vulnerable. One effort to maintain the sustainability of sambar deer is to conduct ex-situ conservation outside its natural habitat. The purpose of this study was to evaluate the management of the implementation of captivity on Jl. Bromo, Bukit Hindu, Jekan Raya, Palangka Raya. Things that need to be evaluated include management aspects of housing, feeding, health care and reproduction as well as the welfare level of Sambar deer in captivity. The requirements for the level of animal welfare are freedom from hunger and thirst, freedom from environmental discomfort, freedom from pain, injury and disease, freedom from fear and stress, and freedom to behave naturally. This study used survey, observation, measurement, interview and literature study methods. The results of the study showed that the level of deer captivity management, in terms of cage management, feed management, and health management, showed a poor category. The animal health biosecurity program has also not been implemented. Only in terms of reproductive management, it is in the good category, because during the 16-year period (2008 to 2024) there was a significant increase in the number of Sambar deer by 45 or an average of 3 per year with a death rate of 2 (4.4%). The birth ratio was 46% male and 54% female. Meanwhile, from the level of animal welfare, it shows that the achievement of the implementation of the welfare of sambar deer in captivity in Palangka Raya City based on the assessment of the five criteria of freedom in animal welfare is in the sufficient category with an average achievement value of 69.5%.